Numerical simulation of an InAsSb based mid-infrared avalanche photodiode - Maurya P.K.; Sunny R.; Chakrabarti P. (My University, 2025)
In the present paper we report a generic numerical model of a separate-absorption-and-multiplication (SAM) avalanche photodiode (APD) that is based on narrow bandgap semiconductors. The model has been applied for theoretical characterization of a proposed P+-GaSb/N-GaSb/no- lnAs0.89Sb0.11n+-lnAs0.89Sb 0.11 SAM-Avalanche photodiode structure for possible application in 2-5 μm wavelength region. The model can be used to estimate and optimize the multiplication gain, excess noise factor and responsivity of SAM-APD based on narrow bandgap semiconductors. The device under investigation exhibits a low dark current (<100 nA at 90% breakdown) and a low excess noise factor (∼2) for a multiplication gain of 10. The gain and excess noise factor can be further improved by optimizing the APD structure. The APD has a high responsivity (>4 A/W) over a wavelength range of 2-4.5 μm for an applied voltage of 6 V. The photodetector exhibits a peak detectivity of 4.2 A/W at 3.8 μm for the same applied voltage. The proposed multiplying MIR APD is expected to outperform conventional photodetectors currently used in optical gas sensors. Copyright © 2007 American Scientific Publishers All rights reserved.